Kepastian Hukum Terhadap Pekerja Mengenai Perselisihan Hak dalam Pelaksanaan Perjanjian Kerja Bersama Pasal Pengupahan Antara Serikat Pekerja Dengan Pihak Perusahaan Ditinjau dari Undang-Undang No 13 Tahun 2003 Tentang Ketenagakerjaan - Haerul Badri; Akbar Sayudi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Legal certainty for workers in fulfilling their rights and obligations when implementing a Collective Labor Agreement often encounters obstacles, this is often due to changes in labor regulations made by the government, in this case the entrepreneur of PT. Kasen Indonesia and the workers' union in the revision of the 2021-2022 Collective Labor Agreement in the wage article agreed on appropriate points to accommodate the interests of each party, but in its implementation they encountered obstacles in the meaning and implementation or so-called rights disputes. The purpose of the research is to determine legal certainty for workers regarding rights disputes and also to determine the resolution of rights disputes regarding the implementation of the Collective Labor Agreement on wages between PT. Kasen Indonesia Employers and the Workers' Union are reviewed from Law No. 13 of Employment of 2023. In writing this thesis, the Juridical-Empirical method is used, namely examining the applicable legal provisions and what happens in reality, using the kualitatif method. Conclusions are drawn inductively and presented descriptively. The results of this research are that legal certainty for workers is provided by management's agreement to implement the Collective Labor Agreement and resolve disputes by making a new formulation regarding wages through bipartite. PKB is formal legal for both parties, and the obligation for the parties is to carry out the provisions that have been agreed in good faith. As explained in Article 126 paragraph 1 of Law 13 of Employment.